A study on the factors that contribute to the level of neighbourhood safety among residents at Kampung Morten, Melaka / 'Azim Mohd Satali and Nabil Fikri Ahmadul Marzuki - Mohd Satali, 'Azim; Ahmadul Marzuki, Nabil Fikri (Faculty of Administrative Science and Policy Studies, 2013)
Neighbourhood safety is one of the crucial agenda that need to be considered of within the residents, it is because people who lived in housing area will face a lot of possibility of bad things happen such as crime, vandalism and etc. To avoiding this kind of bad things happen within the housing area, the residents need to cooperate among themselves and need to keep the bonding among them tighten. Neighbourhood definitions used in previous research have often been data driven.. This is partly due to data limitations, but is also the result of a lack of knowledge of whether and how neighbourhood effects differ. Hence, neighbourhood safety may be simply defined as the awareness of the residents to took care of their neighbourhood. Meaning to say that they keep their bonding with each other among the residents and also with people who involve directly or indirectly in order to keep the housing area safe. The seriousness of the problem of neighbourhood safety should be dealt with immediately. If not, it might be a big problem for the country in the future. In order to do that, the causes neighbourhood problems have to be determined first. This is what the purpose of the research is carried out. There are some factors that are of concern by the researchers which are community cohesiveness factors, safety facilities factors and illegal immigrants factors. Community cohesiveness factors are more concern on the relations and function of the residents inside the community of the housing area. safety facilities factors emphasized by the researchers are the function of the facilities provided by the local government and also the participation of the authorities such as policeman. illegal immigrants factors concern on the behavior of the illegal immigrants who are come in and out the housing area. The researchers believe that these three factors have relation with the level of the neighbourhood safety.